COGNITIVE STYLE “RIGIDITY-FLEXIBILITY OF COGNITIVE CONTROL” AND THE LEVEL INTELLIGENCE INDICATORS - Mun M.V.; Berdibayeva S.K.; Kabakova M.P.; Sakhiyeva F.A.; Dossanova S.S.; Prasetiyawan Dayat; Berdibayev S.K. (Scientific Journal of Pedagogy and Economics, 2021)
Aim of the study. The first goal of the study is to determine the relationship of the cognitive style "rigidity-flexibility of cognitive control" with the level indicators of intelligence. The second goal of this study is to identify possible relationships between "rigidity-flexibility of cognitive control" and the properties of temperament. Materials and Methods. In this work the authors used the Wechsler Adult Intelligence Scale (WAIS), the Stroop color–word-interference task, the Questionnaire of the formal-dynamic properties of individuality (QFDPI, designed by Rusalov V.M.), and 15 heuristic tasks, 5 tasks each in figurative, logical and figurative-logical form (designed by Kulyutkin Y.N., KrutetskiyV.A., Smallian R.). Results. The general success of solving heuristic tasks is determined by a complex of factors, which includes indicators of the flexibility of thinking, intelligence and “intellectual” temperamental properties. The flexibility of thinking is correlated with the level characteristics of intelligence in such a way that high levels of verbal, non-verbal and general intelligence correspond to the flexibility of cognitive control, low values of indicators of intelligence correspond to the pole of rigidity of this cognitive style; intellectually developed subjects are more flexible. Conclusions. The cognitive style of “rigidity-flexibility of cognitive control” can be considered as a metaability. This cognitive style correlates with indicators of temperament and intelligence, and to a certain extent determines the success of solving heuristic tasks.